Symmetric and Asymmetric Decoration of Graphene: Bimetal‐Graphene Sandwiches. (30th March 2015) - Toth, Peter S.; Velický, Matěj; Ramasse, Quentin M.; Kepaptsoglou, Despoina M.; Dryfe, Robert A. W.
Abstract : Low‐dimensional carbon materials, i.e., graphene and its functionalization with a number of semiconductor or conductor materials, such as noble metal nanostructures, have primary importance for their potential exploitation as electro‐active materials, i.e., as new generation catalysts. Here, low‐cost, solution chemistry‐based, two‐step functionalization of an individual, free‐standing, chemical vapor‐deposited graphene monolayer is reported, with noble metal (Au, Pt, Pd) nanoparticles to build up two‐side decorated graphene‐based metal nanoclusters. Either the same metal (symmetric decoration) or different metals (asymmetric decoration) are used for the preparation of bimetal graphene sandwiches, which are adsorbed at the liquid/liquid (organic/water) interface. The successful fabrication of such dual‐decorated graphene‐based metal nanocomposites is confirmed using various microscopic techniques (scanning electron and atomic force microscopies) and several spectroscopic methods (x‐ray photoelectron, energy dispersive x‐ray, mapping mode Raman spectroscopy, and electron energy loss spectroscopy). Taken together, it is inferred from these techniques that the location of deposited metal nanoparticles is on opposite sides of the graphene. Abstract : Graphene is asymmetrically functionalized with different metal nanoparticles . Such dual‐decorated graphene‐based metal nanoclusters are studied using various microscopic techniques and several spectroscopic methods to prove the double‐side decorated monolayer graphene. The preparation of sandwich structures of graphene with two different species opens the way for further asymmetric decoration processes at the polarizable liquid/liquid interface.